2019
DOI: 10.3389/fimmu.2019.00163
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokine Networks in Gastrointestinal Tract Graft vs. Host Disease

Abstract: Graft vs. host disease (GVHD) is the major non-relapse complication associated with allogeneic hematopoietic stem cell transplantation (HSCT). Damage to the gastrointestinal (GI) tract from acute GVHD is a particularly serious event that can result in significant morbidity and mortality. Proinflammatory cytokines play a critical role in the pathophysiology of intestinal GVHD, in part by activating donor T cell populations which subsequently induce tissue damage. In this review, we summarize pre-clinical data d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 100 publications
0
33
0
Order By: Relevance
“…T cells are chief contributors to manifestation and severity of GVHD and act by secreting cytokines that lead to disease onset, especially in the context of cytokine storm 67,68 such as that observed in TBI. Here, we show that bone marrow phenotype correlates tightly with T cell abundance.…”
Section: Discussionmentioning
confidence: 99%
“…T cells are chief contributors to manifestation and severity of GVHD and act by secreting cytokines that lead to disease onset, especially in the context of cytokine storm 67,68 such as that observed in TBI. Here, we show that bone marrow phenotype correlates tightly with T cell abundance.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs and their derivative exosomes have long been known for their immune-modulatory potential and thus have been evaluated in various pre-clinical and clinical settings. A noteworthy, similar condition is observed in Graft versus host disease (GvHD) associated pulmonary disease [56,57]. In a preliminary clinical study, MSC-exosomes were shown to alleviate the symptoms of grade IV GvHD patients [58].…”
Section: Therapeutic Role Of Msc Derived Exosomes In Lung Diseasesmentioning
confidence: 67%
“…We combined treosulfan with fludarabine, thymoglobulin, and cyclophosphamide (60 mg/kg × 2 doses), resulting in a transplant preparative regimen that was lower in intensity than Conv MA regimens but stronger than the previous RIC regimen 9 . Pro‐inflammatory cytokines during HSCT have been associated with adverse outcomes 12‐14 . In animal studies, treosulfan has shown to cause lower levels of inflammatory cytokines compared to busulfan and cyclophosphamide, which may provide an additional advantage in particular in patients with HLH.…”
Section: Discussionmentioning
confidence: 99%